The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/ggi.14553
|View full text |Cite
|
Sign up to set email alerts
|

Judo‐based exercise programs to improve health outcomes in middle‐aged and older adults with no judo experience: A scoping review

Abstract: The practice of judo appears to impact positively on physical performance, muscle strength and flexibility in older people, while also benefiting bone mineral density in middle-aged adults. This scoping review aimed to map the range, scope and type of relevant studies conducted to examine the safety, feasibility and effects of judo interventions on various healthrelated outcomes designed for middle-aged and older adults (≥45 years) with no previous experience in judo. Six databases as well as gray literature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Overall, the results showed that judo training promotes a series of positive outcomes related to psychosocial, functional fitness, and health aspects. Coherently with previous systematic reviews [ 12 , 24 , 29 ], the majority of the experimental studies (90%) showed clear evidence of the positive effects of judo training on health and fitness with advancing age, including significant improvements in fall skills and quality of life. Whilst it is widely recognised that regular physical activity promotes general well-being over the course of life, recently, the COVID-19 pandemic revealed the vital importance of active lifestyles for both mental and physical health, especially for the older population [ 4 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Overall, the results showed that judo training promotes a series of positive outcomes related to psychosocial, functional fitness, and health aspects. Coherently with previous systematic reviews [ 12 , 24 , 29 ], the majority of the experimental studies (90%) showed clear evidence of the positive effects of judo training on health and fitness with advancing age, including significant improvements in fall skills and quality of life. Whilst it is widely recognised that regular physical activity promotes general well-being over the course of life, recently, the COVID-19 pandemic revealed the vital importance of active lifestyles for both mental and physical health, especially for the older population [ 4 ].…”
Section: Discussionsupporting
confidence: 55%
“…As a multicomponent combat sport, judo training represents an extraordinary example of a suitable exercise program for older novice practitioners [ 2 , 23 , 26 , 38 , 59 ]. In fact, judo sessions include coordination and balance exercises performed barefoot, as well as an active engagement in activities and experiences that help older individuals in developing and maintaining their strength (i.e., nage-waza with practitioners moving and often lifting the partner) and flexibility (i.e., ju-no-kata practice with stretching), which could help in contrasting major degenerative aging processes (e.g., sarcopenia, osteoporosis) [ 26 , 29 , 38 ]. The present findings confirm previous results on the perceptual and cognitive benefits of different physical exercises for older people, with older judoka presenting better dynamic visual acuity and peripheral vision with respect to co-aged sedentary counterparts [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the expert’s opinions, coaches have to apply specific strategies and methodologies to achieve positive outcomes (e.g., prevention of fall-related injuries, promotion of wellness and active lifestyle, sense of belonging, and lifelong learning) from an adapted judo training [ 11 , 20 , 22 , 111 ]. A judo training methodology for older adults respecting the general good principles of safety, customizability, progression, completeness, enjoyment, and variety was supported.…”
Section: Discussionmentioning
confidence: 99%
“…Judo (jū = gentle; dō = way) is a martial art and an Olympic combat sport, but more a means of education and a method of personal and social improvement through the execution of various techniques, according to its founder, the Japanese educator Jigoro Kano Sensei. Due to its inner characteristics stimulating coordination, dynamic balance, bone health, and mental control, judo has been considered particularly suitable for older people [ 11 , 16 , 20 , 21 , 22 ]. Based on the principles of “maximum efficient use of mind and body” and “mutual welfare and benefit” [ 23 ], judo encompasses self-defense techniques implemented in group contexts, which improve self-control, discipline, active lifestyles, physical and mental health, and a special group of techniques allowing to fall in a controlled and safe way (i.e., ukemi) [ 10 , 11 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%